HAK ISTRI DALAM HUBUNGAN SEKSUAL MENURUT HUKUM KELUARGA ISLAM - Azmi Ro'yal Aeni; Maulana Ni'ma Alhizbi (Program Studi Hukum Keluarga Islam, 2023)
In marital relations, one of which is sexual relations, Islam puts forward the principles of equality between husband and wife, but in reality, women often treated unfriendly and prone to not fulfilling their rghts, one of which is the right to enjoy sexual relations. This study aims to understand the right to enjoy sexual relations for women in Islam an its relation to communication in marriage, as well as the exposure of ‘aqd tamlik and ‘aqd ibahah in marriage. The research method used in this research s library research with a normative approach. The result of this research is that culture has formed male superiority in sexual relations. Religious texts need to be accompanied by good communication in marriage as bridge for the creation of good husband and wife relatons. ‘Aqd tamlik is marriage with concept of a contract of ownership (the husband owns the wife completely), ‘aqd ibahah means the concept of marriage involving an agreement between the two parties. Keywords: Women's Rights; Marriage Communication; Islamic Family Law